What can humanitarian classes give a present-day schoolchild? - Shapiro, Nadezhda (Voprosy obrazovaniya / Educational Studies Moscow, 2010)
Government demands on teaching literature and history have not been precisely formulated as yet. Possibly, it is not too late to tell now about the fruit of school humanitarian education that teachers organize according to their own ideas of how to do it. Evaluating that experience are men and women who attended the humanitarian class of Moscow Comprehensive School No. 57 in different years. Its former pupils highly appreciate the information and practical habits they received at school but cherish as precious gems what cannot be used in practice)a new picture of the world and the cultural environment and tradition they discovered in class.